Gestão da Qualidade em Arquivos Municipais: A Certificação segundo a ISO 30300 - Luís Miguel Martins Fonseca Perdigão (2019)
This dissertation fits in the field of studies of records management and quality management and has the final purpose of understanding the benefits of implementation, and subsequently certification, of a management system for records based on ISO 30301, at the General Archive of Porto City Council. Firstly, a literature review has been made on the areas of quality management and records management, framing both with the ISO standards previously mentioned, in order to figure out better the concepts related with those fields and in which way the combination of them might be benefic. Later, based on the time spent at the General Archive of Porto City Council, we go deeply into its integrated management system, focusing on describing the quality management system, putting in context the structure, starting from the City Hall as a whole, to later analysing it in a smaller scale and perceiving the work processes of the General Archive, and how quality management is used on a everyday basis. Lastly, after surveying the workers of the general archive, we list some aspects seen as negative and that could be improved if a management system for records like ISO 30301 was implemented alongside the quality management system. Complementary to it, we evaluate which required procedures might already be found due to the interrelationship between standards, and which of them must be added to the integrated management system in order to fulfill the requirements on a process of a hypothetical certification.